Characterization and absorbing properties of oil palm empty fruit bunch filled poly (Acrylic acid–co–acrylamide) superabsorbent polymer composites - Nor Erma Shuhadah Abdul Razak,; Shahrir Hashim,; Abdul Razak Rahmat, (Universiti Kebangsaan Malaysia, 2011)
Oil palm empty fruit bunch graft poly (acrylic acid-co-acrylamide) superabsorbent composite (OPEFB-g-(PAA-co-PAM) SAPC) was synthesized by graft copolymerization of the acrylic acid (AA) and acrylamide (AM) comonomer onto OPEFB fibre using ammonium persulfate (APS) and N,N-methylene bisacarylamide (MBA) as an initiator and crosslinker, respectively. The absorbency in various chloride salt solutions indicated that the absorbency decreased with increasing ionic strength of the salt solutions. Moreover, the absorbency under load (AUL) of SAPC was investigated at various applied loading and results show that, AUL decreased with increasing applied loading. Infrared Spectroscopy (IR) and Thermogravimetric Analysis (TGA) were carried out to confirm the chemical structure and thermal properties of the synthesized superabsorbent, respectively.